EVALUATING MACHINE TRANSLATION QUALITY: A CASE STUDY OF A TRANSLATION OF A VERBATIM TRANSCRIPTION FROM SLOVAK INTO GERMAN - Štefčik, Josef (Vertimo studijos, 2017)
The paper addresses the issue of using online statistical machine translation tools for the translation of specific text types and the problems of their translatability when using automated translation systems. An attempt is made to analyze and evaluate the machine translation of a verbatim transcription from Slovak into German.